STRONGLY LACUNARY CONVERGENCE OF ORDER ? IN NEUTROSOPHIC NORMED SPACES - Kandemir, Hacer Sengul; Mikail, Et; Cakalli, Huseyin (Ivane Javakhishvili Tbilisi State Univ, 2023)
In this paper, the concept of a strongly lacunary convergence of order a in the neu-trosophic normed spaces is introduced. A few fundamental properties of this new concept are investigated.
Keywords: Lacunary convergence; Neutrosophic normed space; Lacunary sequence